Demand-resource evaluations and post-performance thoughts in classical music students: how they are linked and influenced by music performance anxiety, audience, and time - Ludovic Rey; Amélie J. A. A. Guyon; Horst Hildebrandt; Horst Hildebrandt; Angelika Güsewell; Antje Horsch; Antje Horsch; Urs M. Nater; Urs M. Nater; Jeremy P. Jamieson; Patrick Gomez (Frontiers in Psychology)
IntroductionMusicians’ performance experiences range widely, from elation to severe anxiety. In this study, we examined musicians’ performance experiences through the lens of the biopsychosocial model of challenge and threat. According to this model, a challenge state arises when perceived resources meet or exceed perceived demands, while a threat state occurs when demands outweigh resources. These states can be quantified using the Demand Resource Evaluation Score (DRES), calculated as the difference between resource and demand evaluations, with higher values indicating a greater challenge-type response. Although post-event processing is a key factor in maintaining social anxiety, research on factors influencing musicians’ post-performance thoughts remains limited. Additionally, the link between DRES and post-performance thoughts is unknown. This study aimed to determine (1) how DRES is influenced by the general music performance anxiety (MPA) level, audience presence, and time (pre-performance vs. during-performance); (2) how negative and positive post-performance thoughts are influenced by general MPA level and audience presence; and (3) whether DRES predicts post-performance thoughts.MethodsClassical music students (N = 121) with varying levels of MPA performed solo in a private and a public session. We assessed pre-performance and during-performance DRES, and negative and positive post-performance thoughts.ResultsDRES decreased with increasing general MPA level, was lower in public than private sessions, and declined from pre-performance to during-performance. These effects were qualified by a three-way interaction: the effect of general MPA level was strongest before performing publicly, the audience effect was most pronounced at higher general MPA levels before performing, and the time effect was greatest at lower general MPA levels during public sessions. General MPA level was associated with more negative thoughts and fewer positive thoughts. Audience presence increased only negative thoughts. Higher during-performance DRES predicted fewer negative and more positive thoughts both intraindividually and interindividually, with pre-performance DRES showing similar interindividual effects.DiscussionThese findings demonstrate the complex interplay of personal and situational factors in shaping musicians’ challenge and threat experiences. Moreover, high general MPA levels are associated with a general tendency toward more negative and fewer positive post-performance thoughts. Interventions fostering challenge-oriented appraisals may enhance musicians’ post-performance processing, potentially mitigating performance anxiety.